Intercalation of carbamide to globular glauconite by chemical processing for the creation of slow-release nanocomposites - Rudmin, Maxim; Maximov, Prokopiy; Dasi, Evan; Kurovsky, Alexander V.; Gummer, Yana; Ibraeva, Kanipa; Kutugin, Victor; Soktoev, Bulat; Ponomarev, Konstantin; Tararushkin, Evgeny; Makarov, Boris; Ruban, Alexey (Applied clay science)
This article investigates the intercalation of carbamide within globular glauconite involving the chemical activation of glauconite with carbamide solution-gel at varying concentrations of total nitrogen (N). Mineral nanocomposites were prepared with a multitude of novel functions. As the N concentration of the initial solution increased, the proportion of intercalated N enhanced to 8%. A 20% of N concentration in carbamide solution maximizes intercalation. Intercalation occurs in the interlayer of smectite layers (micropores) in glauconite. In nanocomposites, the decrease in specific surface space, total volume pores, and average pore size reflect the absorption of carbamide in meso- and macropores of glauconite globules. Glauconite nanocomposites retain a spherical particle morphology and a distinct microlayer close to the surface. The increased proportion of nitrogen in the microlayers close to the surface indicates a high filtration capacity of the globules. The near-surface microlayer serves as a diffusion channel for the glauconite interior, where new substances are absorbed in the micro- (interlayer) and macropores. The stepwise kinetics of nutrient release, which supports the various forms of carbamide absorption in glauconite, distinguishes the nanocomposites. In addition to N-compounds, glauconite nanocomposites are mineral sources of the available potassium (K) in soils. As a result, chemically manufactured glauconite nanocomposites have some following advantages: the micro-granular mineral form, a permeable inner near-surface microlayer, incubated in micro-, meso-, and macropores N-compounds, and the available K.